Economic, Social, and Cultural Contexts of Early Marriage in Bengkulu Province - Danur Azissah Roesliana Sojais; Jipri Suyanto; Handi Rustandi (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Background: Bengkulu Province is one of the provinces with the highest proportion of early marriages in Indonesia, and it is known that women are vulnerable to domestic violence, pregnancy complications, death during childbirth, and psychological risks, which can have a negative impact on the mother and fetus, both during pregnancy and the child's old age.Objective: This study aims to investigate the determinants associated with early marriage in Bengkulu Province. Method: This study used a cross-sectional study using an online questionnaire as the research tool. The target respondents in this study were mothers who married in Bengkulu Province. The data obtained were analyzed using regression techniques (bivariate and multivariate) to see the indicators associated with early marriage. Results: Factors significantly associated with early marriage were the father's education (AOR: 6.47; 95%CI: 4.67-9.003; P: 0.001), living conditions (AOR: 2.84; 95%CI: 1.75-4.6; P: 0.001), family support (AOR: 2.67; 95%CI: 1.65-4.33; p-value: 0.000), and community perspective (AOR: 2.28; 95%CI: 1.4-3.71; p-value: 0.001). Conclusion: Culture born from a community perspective, family support accompanied by living conditions influenced by the economy, and a father's education greatly affect the incidence of early marriage itself. A program that can raise public awareness of the negative impact of early marriage is needed.